2002
DOI: 10.1128/mcb.22.16.5753-5760.2002
|View full text |Cite
|
Sign up to set email alerts
|

TonEBP/NFAT5 Stimulates Transcription of HSP70 in Response to Hypertonicity

Abstract: While hyperosmolality of the kidney medulla is essential for urinary concentration, it imposes a great deal of stress. Cells in the renal medulla adapt to the stress of hypertonicity (hyperosmotic salt) by accumulating organic osmolytes. Tonicity-responsive enhancer (TonE) binding protein (TonEBP) (or NFAT5) stimulates transcription of transporters and a synthetic enzyme for the cellular accumulation of organic osmolytes. We found that dominant-negative TonEBP reduced expression of HSP70 as well as the transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 48 publications
7
156
2
Order By: Relevance
“…About-250 bp region in the hsp70-2 promoter was responsible for the induction of hsp70 by hypertonic stress The human hsp70-2 promoter region contains three TonE (tonicity-responsive enhancer) sites, which have been reported to play an important role in the response to hypertonicity (Woo et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About-250 bp region in the hsp70-2 promoter was responsible for the induction of hsp70 by hypertonic stress The human hsp70-2 promoter region contains three TonE (tonicity-responsive enhancer) sites, which have been reported to play an important role in the response to hypertonicity (Woo et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…While many types of stress such as heat shock, heavy metals, and amino acids analogues induce both hsp70.1 and hsp70.3 simultaneously, hypertonic stress has been found to induce hsp70.1 selectively (Tanaka et al, 1988;Lee and Seo, 2002;Woo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We report prominent expression of AR, TauT, and SMIT in the perifascicular atrophic fibers of DM, accompanied by increased/induced expression of other known NFAT5 molecular targets HSP70, 27 iNOS, 28 and CCL2. 29 As was the case earlier for iNOS, 30 we could, however, not confirm a significant increase of AR protein levels in DM muscle extracts via western blotting, presumably because of its expression being limited to the affected perifascicular areas.…”
Section: Osmolyte Pathway Activation In Dmmentioning
confidence: 99%
“…It has been also reported that the consensus sequence of the TonE/ORE is the 59-(C/T)GGAANNN(C/T)N(C/T)-39 and/or 59-NGGAAA (A/T)(T/A/G)(C/A/T)(A/C)C-39 in the canine BGT1 gene (16) and/ or AR gene (17,18), respectively. In addition to the BGT1 and AR genes, the TonE/ORE has been identified in the proximal region of the 59-flanking region of stress protein genes, such as Hsp70 (19) and Osp94 (20), which protect cells from the deleterious effects of hyperosmolity. Recent studies on intracellular signaling pathways responsive to hypertonicity have suggested that MAPKs pathways play a role in the cellular mechanisms underling the regulation of gene expression in response to hypertonicity (21)(22)(23)(24).…”
mentioning
confidence: 99%